1975
DOI: 10.1113/jphysiol.1975.sp011178
|View full text |Cite
|
Sign up to set email alerts
|

Calcium content and exchange in frog skeletal muscle.

Abstract: Calcium content and exchange in frog ELD IV muscle were examined employing the efflux technique. 2. Muscle calcium was found to exchange with four time constants, 21‐5 sec 2‐7, 32 and 1244 min. 3. All calcium was found to be exchangeable with more than half the total amount residing in an extracellular compartment. 4. Results obtained from ELD IV muscles and single fibres were identical. 5. Muscle calcium content was found to remain constant up to 20 hr in vitro. 6. Extra exchange of calcium occurs upon contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
4

Year Published

1978
1978
1994
1994

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 14 publications
0
12
4
Order By: Relevance
“…Our results suggest that 45 Ca, identified in radioautographs as bound to LSR (108,109), was in fact bound to Ca-binding proteins . The combined results of the analysis ofthe TC and of the LSR are also inconsistent with the interpretation of Ca" flux data that ascribe a relatively small (0.2 mmol/kg wet muscle), fast exchanging (time constant = 2.7 min) component as representing the Ca content of the TC, and a larger (0.54 mmole/kg wet muscle) slowly exchanging (time-constant = 1,244 min) component to the LSR (54). The relatively low Ca content of the LSR that, in contrast to the TIC, contains little or no calsequestrin (12,51,52,66), does support the conclusion that the free Ca" in the SR is in the low millimolar range (104).…”
Section: The Composition Of the Cytoplasm And Of The Lsr During Tetancontrasting
confidence: 72%
“…Our results suggest that 45 Ca, identified in radioautographs as bound to LSR (108,109), was in fact bound to Ca-binding proteins . The combined results of the analysis ofthe TC and of the LSR are also inconsistent with the interpretation of Ca" flux data that ascribe a relatively small (0.2 mmol/kg wet muscle), fast exchanging (time constant = 2.7 min) component as representing the Ca content of the TC, and a larger (0.54 mmole/kg wet muscle) slowly exchanging (time-constant = 1,244 min) component to the LSR (54). The relatively low Ca content of the LSR that, in contrast to the TIC, contains little or no calsequestrin (12,51,52,66), does support the conclusion that the free Ca" in the SR is in the low millimolar range (104).…”
Section: The Composition Of the Cytoplasm And Of The Lsr During Tetancontrasting
confidence: 72%
“…Whether the increase is due to a Ca binding protein similar to that of the intestinal mucosa (see Introduction) must await further investigation. Extracellular bound Ca has been observed in many other tissues including smooth muscle (Weiss & Goodman, 1969), skeletal muscle (Kirby, Lindley & Picken, 1975), anterior pituitary slices (Moriarity, 1980) and barnacle muscle fibres (Bacigalupo, Luxoro, Rissetti & Vergara, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…There is much evidence that terminal cisternae and longitudinal SR of frog twitch muscle are separated by a diffusion barrier: (a) Winegrad (1968), using autoradiographic techniques, found that calcium movements from longitudinal tubules to terminal cisternae can take more than 20 s after a tetanus, suggesting a diffusion barrier between those structures. (b) Kirby et al (1975), using tracer experiments on single muscle fibers and small muscles, conclude that calcium washes out of the terminal cisternae with a time constant of 2.7 min, whereas it washes out of the longitudinal SR with a time constant of 1,244 min. Winegrad (1970) also found that calcium in the terminal cisternae exchanges with the external medium much more quickly than calcium in the SR.…”
Section: Evaluation Of Modelsmentioning
confidence: 99%